STUDI TENTANG CORAK HABITAT DAN KOMPONEN PENDUKUNG TERHADAP POPULASI RUSA TIMOR (Cervus timorensis, DE BLAINVILLE 1822) DI TELUK BRUMBUN TAMAN NASIONAL BALI BARAT - Made Ari Sanjaya (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2018)
Deer timor (Cervus timorensis) is one of the most widely distributed species in Indonesia, but the population is generally indicated to continue to decline over time due to habitat destruction and hunting pressure, and there are also indications that there is a shift in the pattern of spreading in forest areas including in West Bali National Park. The type of this research is descriptive explorative research by conducting field survey. The result showed that habitat pattern at Savanna Forest Ecosystem at Brumbum Bay of West Bali National Park reached a temperature range of ± 30oC to ± 33oC and moisture range ± 49,75% to ± 73% and light intensity range ± 462,5 lux up to ± 600 lux. The height of the place in Brumbun Bay West Bali National Park reached ± 90 Mdpl. Topography of deer timor habitat is lowland area with semi open type habitat. While the habitat support component of the deer timor population in Brumbun Bay National Park of West Bali is quite good can be seen from the indicators as follows; a). habitat area; b) feed and drink; c) shelter is still available but there are threats that affect the presence of deer in their habitat of wild dogs hunting wildlife in the park, especially deer timor (Cervus timorensis).